Studi Sifat Listrik pada Film GaN Doping Mg yang Ditumbuhkan dengan Metode Metalorganic Chemical Vapor Deposition (MOCVD) Berbantuan Plasma - A. Subagio; Erzam S.H.; Sugianto Sugianto; M. Budiman; M. Barmawi (Institut Teknologi Bandung, 2002)
Mg-doped GaN films have been grown on (0001) sapphire substrates by employing plasma-assisted Metalorganic Chemical Vapor Deposition (MOCVD) method. Trimethylgallium (TMGa) and N2 were used as Ga and N precursors, respectively and bis-cyclopentadienyl magnesium (Cp2Mg) as a p-type doping source. The process of growing thin film was started by deposition the buffer layer on 0.08 sccm TMGa and 140 sccm N2 flow rates. Under this condition a 260 Å thick buffer layer was achieved. The ratio of Cp2Mg and TMGa flow rate was varied 0.3; 1; 2; 5; 7 and 10 %. Hall measurements the show that type of GaN film in 0.3% was n-type, in 1% the type was not clear, while in 2, 5, 7 and 10% GaN films were absolutely of p-type. The 10% Mg-doped GaN film had the highest hole mobility of 55.71 cm2/Vs. It also had the hole concentration of 1.14x1019 cm-3 and resistivity of 9.87x10-3ohm.cm.